Pengaruh Perilaku Konsumen Masyarakat Kabupaten Gresik Terhadap Penggunaan E-Money - Fanani, Ahmad Faizal; Aji, Tony Seno (Jurnal Ekonomika : INDEPENDEN, 2023)
This study aims to identify the influence of cultural, social, personal, and psychological factors on the decision to use e-money in Gresik Regency. E-money can be defined as a "prepaid product or the value of the funds paid is stored in the customer's electronic device. Meanwhile, consumer behavior is an individual action based on personal preference to benefit from the use of goods or services. Each individual has a unique consumption behavior, influenced by by cultural, social, personal, and psychological factors.This study used a quantitative approach with primary data sources obtained through questionnaires with a Likert scale.Analysis was performed using multiple linear regression with the Ordinary Least Square (OLS) model.The results showed that factors culture, social, and psychology have a positive influence on the decision to use e-money in Gresik Regency, however, personal factors do not influence the decision to use e-money.